Analysis of students' cognitive difficulties based on the revised Bloom's taxonomy in solving mathematics problems - Azis, Azis; Handayani, Imelda Tria; Ferniati, Ferniati; Anggriana, Nurmarini; Aisyah, Aisyah (Journal Focus Action of Research Mathematic (Factor M), 2023)
Kesulitan belajar tidak memandang kemampuan intelegensi yang dimiliki siswa. Banyak siswa dengan intelegensi tinggi dapat meraih prestasi belajar yang rendah. Siswa sulit mengerjakan soal yang ada dikarenakan sulitnya memamahami soal, kurangnya mampu menguasai materi yang diajarkan oleh guru disekolah, serta ketika menjelang Ujian, siswa tidak belajar dengan sungguh-sungguh. Tujuan penelitian ini untuk mendeskripsikan tingkat kesulitan kognitif berdasarkan taksonomi bloom revisi dan letak kesulitan belajar matematika siswa pada aspek kognitif pada pelajaran matematika dalam menyelesaikan soal-soal matematika SMP di Kota Baubau. Penelitian ini menggunakan metode survei. Subjek pada penelitian ini adalah siswa kelas IX SMP di Kota Baubau tahun pelajaran 2020/2021. Pengumpulan data dalam penelitian ini dilaksanakan dengan teknik pengukuran dalam bentuk tes diagnostik yang berupa soal-soal Ujian Nasional Matematika tahun pelajaran 2018/2019 yang telah dimodifikasi oleh peneliti dan wawancara untuk mendukung hasil analisis. Berdasarkan hasil penelitian diperoleh kesimpulan: 1) tingkat kesulitan kognitif berdasarkan taksonomi bloom revisi dalam menyelesaikan soal-soal matematika SMP di Kota Baubau dengan skor sebesar 42,43  yaitu berada pada tingkat kesulitan sedang, dan 2) letak kesulitan belajar matematika siswa pada aspek kognitif, yaitu: kesulitan pemahaman faktual dengan persentase interval sebesar 10,48%-20,52%, kesulitan pemahaman konseptual dengan persentase interval sebesar 72,26%-83,74%, dan kesulitan pemahaman prosedural dengan persentase interval sebesar 86,44%-94,56%. Learning difficulties are regardless of a student's intelligence. Many students with high intelligence can achieve low learning achievement. Students find it challenging to work on existing problems due to the difficulty of understanding the questions, the lack of being able to master the material taught by the teacher at school, and when approaching the exam, students do not study seriously. This study aimed to describe the level of cognitive difficulties based on Bloom's revised taxonomy and the location of students' learning difficulties in the cognitive aspect of mathematics in solving junior high school math problems in Baubau City. This research used a survey method. The subjects in this study were grade IX junior high school students in Baubau City in the 2020/2021 academic year. Data collection in this study was carried out using measurement techniques in the form of diagnostic tests in the form of Mathematics National Examination questions for the 2018/2019 school year which had been modified by the researcher and interviews to support the analysis results. Based on the results of the study, the conclusions were obtained: 1) the level of cognitive difficulty based on Bloom's revised taxonomy in solving junior high school math problems in Baubau City with a score of 42.43, which is at a moderate level of difficulty, and 2) the location of students' mathematics learning difficulties in cognitive aspects, namely: factual comprehension difficulties with a percentage interval of 10.48%-20.52%, conceptual comprehension difficulties with a percentage interval of 72.26%-83.74%, and procedural comprehension difficulties with a percentage interval of 86.44%-94.56%.